2003
DOI: 10.1016/s0885-3924(03)00139-8
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-Low Dose Oral Naltrexone Decreases Side Effects and Potentiates the Effect of Methadone

Abstract: Ultra-Low Dose Oral Naltrexone Decreases Side Effects and Potentiates the Effect of MethadoneTo the Editor:The use of N-methyl-D-aspartate (NMDA) receptor antagonists to decrease opioid side effects, potentiate opioid actions, and decrease the development of tolerance has been a topic of substantial interest over the last decade. The pioneering work by Trujillo and Akil suggested that tolerance to opioids could be prevented by the non-competitive NMDA receptor antagonist MK-801. 1 Subsequent studies indicated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
29
0
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 9 publications
0
29
0
2
Order By: Relevance
“…9,12 When considering the clinical studies that did not demonstrate enhanced analgesia by the addition of low doses of naloxone to morphine PCA, it should be noted that the naloxone doses in those studies were considerably higher than the naltrexone doses in this clinical trial. Although naloxone and naltrexone might not be equipotent, the dosing differences in the current clinical trial versus previous studies are substantial and are further augmented by the increased bioavailablility of intravenous administration of the earlier studies compared to the 20% bioavailability of oral naltrexone 13 used in this clinical trial.…”
mentioning
confidence: 88%
See 2 more Smart Citations
“…9,12 When considering the clinical studies that did not demonstrate enhanced analgesia by the addition of low doses of naloxone to morphine PCA, it should be noted that the naloxone doses in those studies were considerably higher than the naltrexone doses in this clinical trial. Although naloxone and naltrexone might not be equipotent, the dosing differences in the current clinical trial versus previous studies are substantial and are further augmented by the increased bioavailablility of intravenous administration of the earlier studies compared to the 20% bioavailability of oral naltrexone 13 used in this clinical trial.…”
mentioning
confidence: 88%
“…7,20,25,26 Clinical experience with opioid antagonists combined with opiates is limited to case reports and a few small clinical studies. 2,3,9,10,12 In one case study, a diabetic polyneuropathy patient, who previously had no pain relief from a variety of treatments, reported profound analgesia when 2 g/ day of naltrexone was added to methadone. 9 The first controlled clinical study demonstrated an opioid-sparing effect and a reduction in side effects by a continuous infusion of naloxone at 0.25 g/kg/h added to morphine administered by patient-controlled analgesia (PCA).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Ultra-low-dose opioid antagonists were also shown to enhance and prolong the analgesic effects of opioids even acutely (Powell et al, 2002;Shen et al, 2002a,b) and to reverse the paradoxical hyperalgesic effect of low doses of opioids to provide strong analgesia (Crain and Shen, 2001). The effects of ultralow-dose opioid antagonists have been extended to small clinical studies or clinical trials showing enhanced analgesia (Joshi et al, 1999;Hamman et al, 2004;Chindalore et al, 2005), opioid sparing effects (Gan et al, 1997), profound analgesia in a severely opioid tolerant patient (Cruciani et al, 2003), and, in a recent Phase III clinical trial, reduced physical dependence (Webster et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…12 Three cases in which naloxone "reset the receptors" in an opioid-tolerant patient with pain and a case in which naloxone caused analgesia are presented.…”
Section: Introduction Pmentioning
confidence: 99%